LEARNING ACHIEVEMENT IS REVIEWED FROM INDEPENDENCE, LEARNING FACILITIES, PARENTAL ATTENTION AND PEER ENVIRONMENT STUDENTS OF SMK NEGERI 1 SRAGEN - Triningsih, Rini; Aryati, Ida; Pawenang, Supawi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine the effect of learning independence, learning facilities, parental attention and peer environment on student achievement in SMK Negeri 1 Sragen. This type of research is causal research with a regression approach, the type of research is quantitative research with a regression research design. The research population of all 12th grade students of SMK Negeri 1 Sragen consisted of 14 groups of 504 students. The research sample for each group was taken by 10 students who had the top ten academic rankings in the hope that they would have better results. Data collection using a questionnaire was analyzed using multiple linear regression analysis assisted by SPSS 23.0 for Windows program. The results showed that learning independence had an effect on learning achievement, learning facilities had an effect on learning achievement, parental attention had no effect on learning achievement, and peer environment had an effect on learning achievement. Suggestions from this research are students, teachers, parents take their respective roles to create independent learning, provide learning facilities, attention and a peer environment so that student learning achievement increases even during the covid-19 pandemic. Keywords: Learning Achievement, Independence, Learning Facilities, Parental Attention, Peer Environment.